Hubungan Kadar C-Organik Tanah Gambut Terhadap Ketersedian Unsur Hara Makro N P K di Perkebunan Kelapa Sawit PTPN IV Unit di Desa Langan Tengah Kecamatan Bebdahara Kabupaten Tanjung Jabung Timur - Yusfaneti, Yusfaneti; Nasution, Hasriati; Saad, Asmadi; Mulyati, Sri (Jurnal Inovasi Global, 2025)
This study aims to analyze the effect of peat thickness, organic C content, and macronutrients (N, P, K) on land productivity in oil palm plantations. The study was conducted at the PTPN IV Oil Palm Plantation, Lagan Tengah Village Unit, Bendahara District, East Tanjung Jabung Regency, using survey and Proportional Random Sampling methods. The parameters observed included peat groundwater level, organic C content, N, P, K nutrient content, peat depth, and peat maturity in oil palm plants aged 6, 11, and 16 years. Data analysis was carried out using the Unpaired Mean Value Test and Simple Linear Regression Test. The results showed a significant relationship between peat depth and groundwater level at the age of 6 years (R = 72.3%) and 11 years (R = 81.0%). The relationship between organic C and total soil nitrogen in oil palm plants aged 6 years (R = 85%) and 11 years (R = 72%) was also significant. In addition, there was a positive relationship between organic carbon and available phosphorus (6-year-old, R = 0.79; 11-year-old, R = 0.65) and total soil potassium (6-year-old, R = 0.80; 11-year-old, R = 0.758). These results demonstrate the importance of peat depth and nutrient management in increasing oil palm productivity.